Democracy and Legal Change - Schwartzberg, Melissa (Cambridge University Press, 2013)
Since ancient Athens, democrats have taken pride in both their power and their proclivity to change their laws. For centuries, political theorists have recognized the distinctively democratic tendency to modify laws, yet this very capacity has given pause to democrats, and they have sought to restrict radically their ability to exercise this authority. As a consequence, democrats have resorted to “entrenchment” – the use of irrevocable laws – as a means of countering their tendency to engage in legal change.